Implementasi Jquery AJAX Untuk Fitur Pendataan Petani pada Website Dutatani - Mau, Wilfridus Bau; Wibowo, Argo; Delima, Rosa (Jurnal Terapan Teknologi Informasi, 2023)
Dutatani is an integrated information system in the agricultural sector developed by a Duta Wacana Christian University team. Dutatani has several subsystems, including the farmer data collection system. The team developed a web-based farmer data collection system. This system was developed using web version 1.0 when requesting or receiving a response from the server. The system needs to carry out loading and reloading the page. The condition results in additional time for processing and loading the whole page. AJAX technology is part of the web generation 2.0. A website can make page changes without reloading the page through this technology. This feature can speed up the reload time of a web page. In this research, AJAX technology has been applied to improve the performance of the farmer data collection system. The system development stage includes literature study, design, development, and evaluation of the system prototype. Evaluation is carried out by comparing system performance before and after implementing AJAX technology. The research results show that AJAX technology can improve the performance of server requests by 5.2%. A significant difference in performance occurs in the amount of data transfer, where AJAX can increase the performance of the data transfer bit size by 86%.